2020
DOI: 10.1177/0003319720969536
|View full text |Cite
|
Sign up to set email alerts
|

Obesity as a Risk Factor for Radiographic Contrast-Induced Nephropathy

Abstract: Contrast-induced nephropathy (CIN) is common. Risk factors include preexisting renal impairment, diabetes, elderly age, and dehydration. In a single-centre prospective study, we investigated which factors are implicated for CIN in patients with peripheral arterial disease due for angiography. Serum creatinine was measured before, 1, 2, and 7 days post-angiography. We also considered the chronic kidney disease stage of the patients at admission and 48 hours post-contrast. All patients received 500 mL normal sal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 46 publications
0
5
0
1
Order By: Relevance
“…Kabeer MA, et al showed that obesity is a risk factor for contrast induced nephropathy. 14 The close relationship between atrial fibrillation and CIN has been demonstrated in recent studies. 15 , 16 Also it has been demonstrated that hypertension, heart failure, age, nephrotoxic drugs, decreased intravascular volume, play important roles in the development of CIN.…”
Section: Discussionmentioning
confidence: 83%
“…Kabeer MA, et al showed that obesity is a risk factor for contrast induced nephropathy. 14 The close relationship between atrial fibrillation and CIN has been demonstrated in recent studies. 15 , 16 Also it has been demonstrated that hypertension, heart failure, age, nephrotoxic drugs, decreased intravascular volume, play important roles in the development of CIN.…”
Section: Discussionmentioning
confidence: 83%
“…In addition, similar to the results of previous studies, CIN was found to be higher in patients with AF and anterior MI (AMI) in our study. 4,13…”
Section: Discussionmentioning
confidence: 99%
“…In addition, similar to the results of previous studies, CIN was found to be higher in patients with AF and anterior MI (AMI) in our study. 4,13 The pathophysiology behind the development of CIN is not yet fully understood. Recent studies have argued that factors such as increased systemic inflammation, oxidative stress, acidosis, and hyperglycemia play a role.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…На это направление исследований было выделено огромное количество средств, и очень большое количество пациентов подверглось исследуемым вмешательствам, включая N-ацетилцистеин, бикарбонат натрия, жидкостную нагрузку, статины, витамин С, вазоактивные препараты, теофиллин, прекондиционирующую ишемию и заместительную почечную терапия, но ни один из них не лишен побочных эффектов [4]. Помимо перипроцедурной гидратации, которая, по-видимому, снижает, но не полностью предотвращает риск повреждения почек после введения рентгеноконтрастных средств, результаты применения других препаратов, таких как дофамин, маннит, Nацетилцистеин и каптоприл, аллопуринол неоднозначны [5][6][7]. В клинических рекомендациях KDIGO по ОПП с целью профилактики КИ-ОПП наряду с внутривенным восполнением объема циркулирующей крови физиологическим раствором натрия хлорида или растворами натрия бикарбоната рекомендуется использовать пероральную терапию N-ацетилцистеином в сочетании с внутривенным введением изотонических растворов кристаллоидов [8].…”
Section: Introductionunclassified